Treatment of drooling with sublingual atropine sulfate in children and adolescents with cerebral palsy - Bruno L. Scofano Dias; Alexandre R. Fernandes; Heber de S Maia Filho (Arquivos de Neuro-Psiquiatria)
ABSTRACT Atropine sulfate blocks the muscarinic receptors in the salivary glands and leads to reduced saliva production. There are no published studies about its use in children with cerebral palsy. Objective To report the effect of sublingual atropine sulfate to treat drooling in children with cerebral palsy by comparing the results of the Drooling Impact Scale in a non-controlled open clinical trial. Results Twenty-five children were assessed. The difference in the mean scores of the pre- and post-treatment scales reached statistical significance. There was a low frequency of side effects compared to studies with other anticholinergics. Conclusion The use of sublingual atropine sulfate seems to be safe and there is a reduction in the Drooling Impact Scale score, which suggests efficacy in the treatment of drooling in children and adolescents with cerebral palsy. Our results should be replicated in randomized, placebo-controlled studies with larger numbers of participants.